2009
DOI: 10.1375/s132601110000082x
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Indigenous Knowledge in Tertiary Science Education: A Case Study of Canadian Practices in Indigenising the Curriculum

Abstract: In Australia, Indigenising the curriculum is increasingly acknowledged as a possible avenue for addressing Indigenous under-representation in tertiary science education in a culturally appropriate and relevant manner. While no Australian university has implemented such a program, there is much to be learnt about the inherent complexities of Indigenising curriculum before it is pursued. In Canada, however, innovative university programs have been implemented that imbed Indigenous knowledge into the curriculum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…Indigenous knowledges and epistemologies are valued and represented across the academic agenda (Sarra et al 2011;Smith 2003;Rigney 2001Rigney , 2006Matthews 2012;Matthews et al 2005). The key characteristics of this professional learning community include plurality of knowledges, values and ways of knowing; shared values and vision; collective responsibility for Indigenous Education; collaboration focused on learning in curricula and pedagogy; individual and collective professional learning; and reflective professional enquiry and support networks (Kinnane et al 2014;Miller et al 2012;Hauser et al 2009;Gunther 2015). This project built a culture of support, collaboration and collective professional learning.…”
Section: Professional Learning Community For Institution Changementioning
confidence: 99%
“…Indigenous knowledges and epistemologies are valued and represented across the academic agenda (Sarra et al 2011;Smith 2003;Rigney 2001Rigney , 2006Matthews 2012;Matthews et al 2005). The key characteristics of this professional learning community include plurality of knowledges, values and ways of knowing; shared values and vision; collective responsibility for Indigenous Education; collaboration focused on learning in curricula and pedagogy; individual and collective professional learning; and reflective professional enquiry and support networks (Kinnane et al 2014;Miller et al 2012;Hauser et al 2009;Gunther 2015). This project built a culture of support, collaboration and collective professional learning.…”
Section: Professional Learning Community For Institution Changementioning
confidence: 99%
“…The lack of visibility or absence of indigenous knowledge in an academic curriculum can make it inaccessible Museum Management and Curatorship 141 or irrelevant to indigenous people (Hauser, Howlett, and Matthews 2009). Conservation pedagogy is largely based on Eurocentric academic disciplines such as science, art history, and archaeology.…”
Section: Academic Programs In Conservationmentioning
confidence: 99%
“…Prior research has addressed issues surrounding general education for Indigenous students (Harris, 2000;Bartlett, 2007;Hauser et al, 2009) and students' studies of accounting in general (Mladenovic, 2000;Jackling and Calero, 2006). While no studies of accounting education for Australian Indigenous students were found, extant literature allows us to consider possible impediments to Indigenous studies of accounting from three perspectives: perceptions of accounting being predominantly numbers-based, issues pertaining to Indigenous education in general and the clash of cultures.…”
Section: Potentially Pertinent Issues From Prior Researchmentioning
confidence: 99%
“…The Australian education system will play a significant role in the under-representation of Indigenous people in accounting studies, due to the Australian education system failing Indigenous students (Bartlett, 2007). At all levels of schooling Indigenous students continue to be underrepresented (Hauser et al, 2009).…”
Section: Indigenous Educationmentioning
confidence: 99%